GPS-TEC observations over Nepal during the Total Solar Eclipse on 22 July 2009 - Shrestha, A. N.; Migoya-Orue, Y. (Journal of Nepal Physical Society, 2021)
This paper explores the ionospheric response in terms of Total Electron Content (TEC) during the 22 July 2009 Total Solar Eclipse. Using the data stored at Biratnagar (BRN2), Ramite (RMTE), Dhangadhi (DNGD), Nepalganj (NPGJ), and Taplejung (TPLJ) Global Positioning System (GPS) stations, the ionospheric activity was investigated through changes in TEC. Our research is based on GPS-TEC measurements from a widely dispersed GPS network across various geographical locations in Nepal, taking place on July 17-21 as a pre-event, July 22 as the main event, and July 23-27 as a post-event. The analysis reveals that the reduction in the TEC level is proportional to the magnitude of the total solar eclipse. The variation of the TEC depends on latitude as well as longitude. We found that TEC depletion was up to 5% from pre-event to main-event and up to 30% from main-event to post-event during the totality of the eclipse. The eclipse was accompanied by the 10-hour geomagnetic storm in Nepal, which was the explanation for the TEC upgrade to 50% on the main event day from pre-event and decreased by 25% from main-event to post-event. The result obtained in this work demonstrates the influence of the eclipse/storm on the variation of TEC.